Simultaneous Effect of Ultrasonic and Chemical Treatment on the Extraction of Nanocellulose From Sugarcane Bagasse - A'yunil Hisbiyah; Lilik Nurfadlilah (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2021)
The focus of this study was the simultaneous effect of ultrasonic and chemical treatment on the extraction of nanocellulose from sugarcane bagasse. Ultrasonic waves can accelerate the dispersion process of nanocellulose particles so that extraction runs faster and is environmentally friendly. The bagasse was treated by chemical treatment with ultrasonic waves, and then the nanocellulose was prepared using acid hydrolysis with ultrasonic waves. The effect of ultrasonication was investigated. The crystallinity of sugarcane bagasse, cellulose, and nanocellulose was analyzed by X-ray diffraction. Based on the diffractogram, there was an increase in the crystallinity of nanocellulose. The chemical composition of extracted cellulose and nanocellulose was analyzed by Fourier-transformed infrared spectroscopy. The results of the analysis showed that lignin and hemicellulose were removed from the bagasse during the extraction process. The analysis results also showed that the breaking of intramolecular hydrogen and glycosidic bonds occurred during the hydrolysis process. The morphology of bagasse, cellulose, and nanocellulose was analyzed by Scanning electron microscopy. While the particle size of nanocellulose was analyzed by the Particle Size Analysis instrument. The average size of nanocellulose particles was 132.67 nm.